Overcoming heuristics that hinder people’s acceptance of climate-change-mitigation technologies - Blöbaum, Anke; Schmidt, Karolin; Böcher, Michael; Arlinghaus, Julia; Krause, Friederike; Matthies, Ellen (Frontiers in Psychology, 2025)
The overall research objective of the present study is the investigation of the effects of a strongly expressed restriction-oriented climate change mitigation heuristic (SER heuristic) on people’s attitude toward and acceptance of climate change mitigation technologies such as Carbon Capture and Utilization (CCU). Furthermore, we want to examine the effects of a scenario-based communication intervention approach on the promotion of a supportive attitude toward and acceptance of CCU, especially referring to people characterized by a SER heuristic. Against this background, we present empirical findings based on an online experiment including a scenario-based intervention in an initial sample of 401 German participants. In line with our expectations, our findings show that participants characterized by a SER heuristic report a significantly lower supportive attitude toward CCU as well as a lower acceptance of CCU, compared to participants who are not characterized by a SER heuristic. Furthermore, our findings imply the examined scenario-based communication intervention approach to be an effective tool for the promotion of participants’ supportive attitude toward CCU and acceptance of CCU. Taken together, the present study provides further valuable insights for the promotion of people’s supportive attitude toward as well as of their acceptance of necessary new climate change mitigation technologies such as CCU.